MEDIA DAN BUDAYA POP - Parapat, Nelson Halong (Istek Widuri Jakarta, 2017)
This paper presents a description the media is now growing rapidly as a result of technological advances media. The ability of media technology currently lead the media to reach the public with a very wide area coverage. Likewise, the media has the ability updating media content quickly. Such media capabilities result in a high media speed in reaching the wider community and updating the information society gains, thus creating community dependence on the media.However, the dependence of the public to the media used by the media owners to profit as much as possible in order to maintain the existence of the media. Media managers produce media content in such a way that makes the media a necessity that must be met by the community because of addiction to consume media content that catapulted the delusion and imagination of citizens. The existence of such a society signifies that society is in what is known as false consciousness. This phenomenon appears with the emergence of pop culture, for example with the outbreak of K-Pop in Indonesia. So it's not surprising that today often encountered young people in Indonesia featuring a style of clothing, hair and make-up artists face as musicians and actors of South Korean soap operas.It is not forbidden to live like a K-Pop. But to be scrutinized whether to apply this kind of pop culture will be more beneficial or detrimental to the public. To raise public awareness, needs to be improved socialization and dissemination regarding media literacy for society, namely the ability of people to access as well as analyzing the impact of the media for the life of society itself.